A rare haplotype of the GJD3 gene segregating in familial Meniere’s disease interferes with connexin assembly - Alba Escalera-Balsera; Paula Robles-Bolivar; Alberto M. Parra-Perez; Silvia Murillo-Cuesta; Han Chow Chua; Lourdes Rodríguez-de la Rosa; Julio Contreras; Ewa Domarecka; Juan Carlos Amor-Dorado; Andrés Soto-Varela; Isabel Varela-Nieto; Agnieszka J. Szczepek; et al. (Genome Medicine)
Abstract Background Familial Meniere’s disease (FMD) is a rare polygenic disorder of the inner ear. Mutations in the connexin gene family, which encodes gap junction proteins, can also cause hearing loss, but their role in FMD is largely unknown. Methods We retrieved exome sequencing data from 94 individuals in 70 Meniere's disease (MD) families. Through gene burden analysis, we calculated the enrichment of rare variants (allele frequency < 0.05) in connexins genes in FMD individuals compared with the reference population. The connexin monomer and the homomeric connexon structural models were predicted using AlphaFold2 and HDOCK. RT-qPCR and immunofluorescence were done in mice cochleae to identify expression of the mouse ortholog candidate gene Gjd3. Results We found an enrichment of rare missense variants in the GJD3 gene when comparing allelic frequencies in FMD (N = 94) with the Spanish reference population (OR = 3.9[1.92–7.91], FDR = 2.36E-03). In the GJD3 sequence, we identified a rare haplotype (TGAGT) composed of two missense, two synonymous, and one downstream variant. This haplotype was found in five individuals with FMD, segregating in three unrelated families with a total of ten individuals; and in another eight MD individuals. GJD3 encodes the gap junction protein delta 3, also known as human connexin 31.9 (Cx31.9). The protein model predicted that the NP_689343.3:p.(His175Tyr) missense variant could modify the interaction between connexins and the connexon assembly, affecting the homotypic GJD3 gap junction between cells. Our studies in mice revealed that Gjd3—encoding Gjd3 or mouse connexin 30.2 (Cx30.2)—was expressed in the organ of Corti and vestibular organs, particularly in the tectorial membrane, the base of inner and outer hair cells and the nerve fibers. Conclusions The present results describe a novel association between GJD3 and FMD, providing evidence that FMD is related to changes in the inner ear channels, and supporting a new role of tectorial membrane proteins in MD.